Utilization of riverine organic matter by macrobenthic communities in a temperate prodelta - Szczepanek, Marta; Silberberger, Marc J.; Koziorowska-Makuch, Katarzyna; Kędra, Monika (Frontiers in Marine Science, 2022)
Macrobenthos is an important component of organic carbon storage and energy flow in marine systems, including these impacted by riverine discharge and high share of allochthonous organic matter (OM). Changing environmental conditions, such as lower precipitation and snow cover duration, may affect patterns of riverine input, therefore it is crucial to know how benthic communities utilize different OM sources in areas affected by rivers. Using Bayesian stable isotope mixing models, we assessed the diet composition of common macroinvertebrates forming benthic communities in the transition zone of one of the largest river outlets in the Baltic Sea region, the Vistula River prodelta. Furthermore, we analyzed the spatial and temporal variability in the biomass-weighted resource utilization by those communities. Contribution of riverine OM to the particulate OM in Vistula prodelta decreases with increasing depth. Despite similar distances to the river mouth, the relative contribution of riverine OM to the diet of all studied taxa also decreases with increasing depth, which corresponds to organic matter composition in prodelta waters. Nevertheless, due to synchronous structural changes in benthic communities, and changes in the feeding modes of dominant species, particularly Macoma balthica and Hediste diversicolor, the riverine organic carbon share in the biomass of benthic communities often remains the highest in the deepest prodelta parts. Our study corroborates that benthic primary consumers act as a gateway for riverine organic matter into the marine food web and illustrates that sediment properties and resource partitioning affects spatial structure of benthic communities and their abilities to utilize allochthonous OM.